Education, the Dream that is Materializing - Annamalai, Visalaakshi (Kathmandu School of Law Review, 2019)
The right to education is a fundamental aspect of human rights. It shapes life for a better tomorrow with a chance of an increase in better employment opportunities. It not only instills hope for a brighter future but also leads to the realization of other rights.1 Progress in human life is impossible without education, but despite this fact, refugees struggle to have access to education. Importance of the right to education increases when it comes to refugees because of its ability to uplift the standard of living. This paper will look at the right to education as a concept and the meaning attributed to the word education. It will shed light on the nature of the right; whether it is a socio-economic and cultural right or a political right. The paper will further examine international instruments which recognize the right to education in emergencies and comprehend how it has been applied to the case of refugees. It points out two positive examples where access to education has been provided by community-based organizations in collaboration with NGOs, governments, and other organizations. The paper acknowledges the barriers to higher education but is not ignorant of the fact that there is progress today as compared to forty years ago. The paper concludes that despite the conscious movement of the international community towards the right to education of the refugees, there is much that has to be done for the complete realization of this right.